Has COVID-19 Delayed the Diagnosis and Worsened the Presentation of Type 1 Diabetes in Children? - Rabbone, Ivana; Schiaffini, Riccardo; Cherubini, Valentino; Maffeis, Claudio; Scaramuzza, Andrea (Diabetes care, 2020)
To evaluate whether the diagnosis of pediatric type 1 diabetes or its acute complications changed during the early phase of the coronavirus disease 2019 (COVID-19) pandemic in Italy. This was a cross-sectional, web-based survey of all Italian pediatric diabetes centers to collect diabetes, diabetic ketoacidosis (DKA), and COVID-19 data in patients presenting with new-onset or established type 1 diabetes between 20 February and 14 April in 2019 and 2020. Fifty-three of 68 centers (77.9%) responded. There was a 23% reduction in new diabetes cases in 2020 compared with 2019. Among those newly diagnosed patients who presented in a state of DKA, the proportion with severe DKA was 44.3% in 2020 vs. 36.1% in 2019 ( = 0.03). There were no differences in acute complications. Eight patients with asymptomatic or mild COVID-19 had laboratory-confirmed severe acute respiratory syndrome coronavirus 2. The COVID-19 pandemic might have altered diabetes presentation and DKA severity. Preparing for any "second wave" requires strategies to educate and reassure parents about timely emergency department attendance for non-COVID-19 symptoms.